Serum testosterone level and active caspase-3 of Leydig cells of diabetic Sprague-Dawley male rats after administration of soybean (Glycin max) powder suspension - Sri Kadarsih Soejono, Wiyadi Dicky Moch. Rizal (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Diabetes mellitus (DM) is known as the main death cause in the world. This disease causes acuteand chronic complication. The common chronic complication on male reproduction system isthe decrease of testosterone level. This hormone is produced in the Leydig cells. Soybeans(Glycin max) has been used in the management of DM to maintain blood glucose level. However,the effect of soybean on serum testosterone level is still unclear. The aim of this study was toevaluate serum testosterone level and caspase-3 active of Leydig cells of diabetic Sprague-Dawley (SD) male rats model induced by streptozotocine (STZ) after oral ingestion of soybeanpowder suspension. This was an experimental study with pre and post test control group design.Thirty SD male rats, aged 11-12 weeks with body weight (BW) of 200-250 g were divided into 5groups with 6 rats in each group. The first group (G1) was normal rat control and the secondgroup (G2) was diabetic rat control. The third to fifth group (G3, G4 and G5) were diabetic rattreatment with oral ingestion of soybean powder suspension that was given once a day during 4weeks with dose of 400; 800 and 1600 mg/kg BW, respectively. The serum testosterone levelwas measured by an ELISA and active caspase-3 of Leydig cells were measured by animmunohistochemistry method. The result showed that the serum testosterone level and activecasapse-3 Leydig cells of diabetic rats model induced by STZ were not significantly differentafter oral ingestion of soybean powder suspension with dose of 400, 800 and 1600 mg/kg BW(p>0.05). In conclusion, soybean powder suspension did not affect the serum testosteronelevel and active caspase-3 Leydig cells in diabetic rats.Keywords: diabetes - soybean - phytoestrogen - testosterone - active caspase-3